KINERJA AGROINDUSTRI KERIPIK PENERIMA DAN BUKAN PENERIMA KREDIT PROGRAM KEMITRAAN BINA LINGKUNGAN (PKBL) PT PERKEBUNAN NUSANTARA VII DI SENTRA INDUSTRI KERIPIK BANDAR LAMPUNG - Mulia Wulandari; Wan Abbas Zakaria; Zainal Abidin (Lampung University, 2017)
This study aims to analyze the difference of agro industrial profit and performance between credit’s recipients and non-recipients of PKBL provide by PTPN VII and the effectiveness of PKBL program. This study is a case study at the Central of Chips’ Industri in Bandar Lampung that has been chosen purposively with consideration that this region is located under the guidance of PTPN VII in which respondents consisted of 32 industries both producers and traders of Telo Rejeki group members. The data is analyzed by descriptive quantitative analysis. The result study showed that the profit of credits’ recipients is higher than non-recipients one, the agro industrial performance of both credits’ recipients and non-receipients of PKBL based on productivity were on good categories. Based on the capacity, the performance of credits’ recipients of PKBL was on good category, while that of non-recipients PKBL were not in good category. In terms of realization and achievement of the overall objectives, PKBL PTPN VII program was quite effective. The highest effectiveness of the program was education and training program.Key words: agroindustry, effectiveness, performance, program